Effects of different repeated sprint-training frequencies in youth soccer players - Rey, Ezequiel; Padrón-Cabo, Alexis; Costa, Pablo B.; Lago-Fuentes, Carlos (Biology of Sport, 2019)
The aim of this study was to determine the effects of 2 different repeated-sprint ability (RSA) training frequencies (2 RSA sessions per week [RSA2D] or 1 RSA session [RSA1D]) under volume-equated conditions on sprint and RSA performance in under‑15 (U15) soccer players. Twenty-seven youth male soccer players (age: 12.29±0.47 years; height: 158.35±10.86 cm; weight: 45.08±8.05 kg) were randomly assigned to RSA2D (n=14) or RSA1D (n=13) groups. The players performed the same RSA training for 6 weeks, and only the training frequency differed between the groups. Before and after the training period, 5 m sprint, 10 m sprint, 20 m sprint and the RSA test were assessed. No significant time × group interactions were observed (p>0.05). Within-group analysis showed significant improvements in 20 m sprint (p=0.046, partial eta squared [ηp 2] = 0.150, large) and RSA average time (p=0.001, ηp 2=0.438, large), fastest time (p=0.012, ηp 2=0.229, large), and total time (p=0.001, ηp 2=0.438, large) from pre-test to post-test in RSA1D and RSA2D groups. However, no significant pre-post changes (p>0.05) were found in 5 m and 10 m sprint tests. In the between-group analysis, there were no significant differences between RSA1D and RSA2D groups in any variable. In conclusion, the current findings suggest that 6 weeks of RSA training 1 or 2 times per week in addition to typical soccer training produced significant and similar improvements in sprint and RSA performances. This information could be useful for coaches when planning training sessions during congested fixtures of soccer competitions or in periods when the emphasis should be placed on other physical qualities.